A refitting experiment on long bone identification. (23rd March 2021) - Morin, Eugène; Boileau, Arianne; Ready, Elspeth
Abstract: Refitting is an important analytical tool in archaeology that can yield valuable information on site formation processes and on the range of activities practiced at a site, including tool production, tool curation, and discard behavior, among others. In the present paper, we use refit data from a control assemblage of red deer ( Cervus elaphus ) long bones to assess problems of specimen identification and representation in an experiment where bones were processed for marrow. Three goals motivated this experiment: (i) to assess how different methods of NISP (number of identified specimens) calculation affect comparisons of the relative abundances of long bone regions, (ii) to evaluate whether long bone shaft regions vary with respect to the probability of identification, and (iii) to ascertain the potential refit rate for a well‐preserved and fully‐collected sample of faunal specimens. Our results show no statistical differences in terms of patterns of skeletal representation between the two methods of NISP calculation (single vs. multiple NISP counts) that we assessed. Our data also indicate that the shape, particularly the cross‐section, of fragments clearly impacts the probability of identification and refitting. Moreover, the refitting experiment reveals that, in ideal conditions, a majority of specimens (>95%) from the NISP sample can be refitted, which leads to largely reconstructed skeletal elements. Thus, the comparatively very low refit rates recorded in archaeological sites, including samples that are well preserved, suggest that the often limited extent of excavations, along with offsite discard and/or extensive sharing of parts, substantially reduce the possibility of finding refits in a faunal sample.